A Spiritual Pilgrimage to a Celtic Homeland: Searching and Internalising in Grief from Stone to Sea. A Collaborative Autoethnography - Lewis, Laura (The international journal of religious tourism and pilgrimage, 2025)
This collaborative autoethnography poses the research question; How does one’s experience of grief and anticipatory grief mobilise pilgrimage journeys to ancestral homelands? Two theoretical constructs found in the academic literature related to grief and loss are explored for their influence on both authors’ respective pilgrimage journeys to the Celtic ancestral homeland of their deceased and ‘vanishing’ fathers in Wales and Ireland. The theoretical constructs explored through an extensive review of paternal personal documents of one author (Laura), revealed thematic ideas that could be best understood through an elaboration of the academic literature(s) that inform understandings of grief and bereavement. These being: 1) Searching for the deceased or ‘vanishing’ other in grief, and 2) The process of internalising those who are no longer with us. For both authors these two conceptual understandings were instrumental in mobilising pilgrimage journeys to Celtic paternal homelands. For myself (Laura), encounters with Aberystwyth University, St David’s Cathedral and small chapels in the Welsh countryside where ancestral relations were interred were organised more than two decades after the death of my father. For Eunice, a pilgrimage journey to Ireland decades earlier with her living, recently diagnosed (Alzheimer’s disease) but ‘vanishing’ elderly father was similarly shaped by these two theoretical considerations in grief / anticipatory grief. Further expansion of these ideas allows for a deeper understanding of the personal and generalisable motivations that influenced the mobilisation of two separate and distinct pilgrimages to the Celtic ancestral homelands of the authors’ beloved fathers.